IMPLEMENTATION OF FACILITIES AND INFRASTRUCTURE DEVELOPMENT BASED ON TOTAL QUALITY MANAGEMENT (TQM) IN SMP IT MASJID SYUHADA, YOGYAKARTA - Tiarani Mirela; Suwadi; Amirrudin (al-Afkar, Journal For Islamic Studies, 2022)
The advancement of an educational institution is supported by many things, including educational facilities and infrastructure. Complex problems that occur in meeting the standardization of educational facilities and infrastructure in an educational institution are quite high at 88.8% in 2016. SMP IT Masjid Syuhada Yogyakarta has not been optimal in implementing facilities and infrastructure, the school continues to innovate in dealing with these problems and also continue to make improvements to achieve the maximum possible goals. the existence of TQM / Total Quality Management offers better management in various ways so that a school is able to be more creative, innovative, and dare to take big steps to move forward effectively and efficiently to bring about change. So that it can be seen that an educational institution that uses total quality management in an educational institution will lead to better goals.